Enhancing conceptual understanding and learning skills: The role of strategy, motivation, teacher support, and self-efficacy - Ummiy Fauziyah Laili; Syamsul Huda; Atika Anggraini; Fareza Chandri Maharani; Luthfiyatul Muniroh; Rofiqul Umam (Journal of Advanced Sciences and Mathematics Education, 2025)
Background: Effective learning involves more than mere exposure to information; it requires learners to engage strategically, be motivated, and operate within supportive environments. In junior high school science education, students often face challenges in developing a deep conceptual understanding and acquiring scientific skills. Addressing this issue calls for the implementation of learning strategies that promote active engagement and student-centered learning. Aim: This study aims to investigate the impact of the Reading, Questioning, and Answering (RQA) learning strategy on students’ conceptual understanding and science learning skills. It also explores the role of learning motivation, teacher support, and self-efficacy in supporting students' learning processes. Method: A quantitative research design was employed, utilizing the Partial Least Squares (PLS) analysis approach. The sample consisted of 40 junior high school students selected through a saturated sampling technique. Data were gathered through questionnaires, classroom observations, and documentation, and analyzed using SmartPLS software to assess the relationships among the studied variables. Result: The results revealed that the RQA learning strategy significantly influences students’ conceptual understanding and science learning skills. While learning motivation, teacher support, and self-efficacy also have positive effects, the RQA strategy was identified as the most influential factor in enhancing science learning outcomes.Conclusion: The findings underscore the importance of innovative and student-centered learning strategies, such as RQA, in improving science education at the junior high school level. These insights are valuable for educators and curriculum developers in designing more interactive and supportive learning environments that foster deeper understanding and scientific competence among students.